Brain pericytes serve as microglia-generating multipotent vascular stem cells following ischemic stroke. Issue 1 (December 2016) - Sakuma, Rika; Kawahara, Maiko; Nakano-Doi, Akiko; Takahashi, Ai; Tanaka, Yasue; Narita, Aya; Kuwahara-Otani, Sachi; Hayakawa, Tetsu; Yagi, Hideshi; Matsuyama, Tomohiro; Nakagomi, Takayuki
Abstract Background Microglia are the resident macrophage population of the central nervous system (CNS) and play essential roles, particularly in inflammation-mediated pathological conditions such as ischemic stroke. Increasing evidence shows that the population of vascular cells located around the blood vessels, rather than circulating cells, harbor stem cells and that these resident vascular stem cells (VSCs) are the likely source of some microglia. However, the precise traits and origins of these cells under pathological CNS conditions remain unclear. Methods In this study, we used a mouse model of cerebral infarction to investigate whether reactive pericytes (PCs) acquire microglia-producing VSC activity following ischemia. Results We demonstrated the localization of ionized calcium-binding adaptor molecule 1 (Iba1)-expressing microglia to perivascular regions within ischemic areas. These cells expressed platelet-derived growth factor receptor-β (PDGFRβ), a hallmark of vascular PCs. PDGFRβ+ PCs isolated from ischemic, but not non-ischemic, areas expressed stem/undifferentiated cell markers and subsequently differentiated into various cell types, including microglia-like cells with phagocytic capacity. Conclusions The study results suggest that vascular PCs acquire multipotent VSC activity under pathological conditions and may thus be a novel source of microglia.